(untitled) (Bangladesh Journal of Agricultural Research, 2016)
An experiment was conducted at the field of USDA-Alliums project, Bangladesh Agricultural University, Mymensingh to study the effect of tillage and mulches on the growth and yield of garlic. The experiment consisted of three tillage conditions (conventional, puddling and zero tillage) and four mulches (control, rice straw, water hyacinth and Curcuma amada leaf). The results revealed that different mulches had remarkable contributions on the growth and yield of garlic. The highest values of growth parameters as well as bulb yield were obtained from rice straw mulch identical with that of water hyacinth mulch. Different tillage also had significant influence on yield and yield contributing traits of garlic. Garlic cultivated under zero tillage showed remarkable variation in terms of percent emergence. Puddling and zero tillage practices resulted in higher yield compared to the conventional tillage. It was also noticed that both the tillage conditions as well as mulches showed profound effects on the yield and yield contributing parameters. Moreover, the highest net return (196647Tk. /ha) and the highest BCR of 2.90 was obtained from zero tillage with rice straw. Bangladesh J. Agril. Res. 41(1): 53-66, March 2016